A portable and miniaturized lab-on-fiber sensor based on a responsive Fabry–Perot resonance cavity for the detection of thiocyanate. Issue 38 (15th September 2022) - Wang, Guangrong; Lv, Zhixin; Wang, Chengyang; Chen, Dan; Zhang, Xuemin; Zhang, Liying; Fan, Fuqiang; Fu, Yu; Wang, Tieqiang
Abstract : A portable lab-on-fiber sensor was constructed through integrating a responsive metal–insulator–metal resonator on the end surface of an optical fiber tip for the detection of SCN − . Abstract : Thiocyanate (SCN − ) detection is highly significant because of the toxicity of SCN − . Herein, a portable and miniaturized lab-on-fiber (LOF) sensor is reported for the detection of SCN − through integrating a Fabry–Perot (F–P) optical resonance cavity based on anionic-responsive metal–insulator–metal (MIM) onto an optical fiber tip. The responsive MIM optical resonance cavity is constructed with an intermediate cationic polymer brush layer (poly[2-(methacryloyloxy)ethyl] trimethylammonium chloride, PMETAC) and two silver layers via a facile in situ "layer-by-layer" construction method. When the fabricated LOF sensor was immersed in SCN − solutions, an obvious reflection dip shift can be observed, which is feasible for the quantitative detection of SCN − . What's more, the fabricated LOF sensor exhibits outstanding selectivity and anti-interference against other interfering anions. Furthermore, the fabricated LOF sensor also displays other excellent advantages endowed by the polymer brush film, such as a fast response rate and outstanding reproducibility. Therefore, it is believed that the fabricated miniaturized LOF sensor would show great potential as a portable sensor in future applications, such as environmental monitoring and clinical diagnosis.